High Performance Work Systems and Adaptive Performance: Evidence from Knowledge Intensive Organizations - Kesumayani, Heni (SAFE-Network, 2026)
The increasing dynamism of knowledge-intensive organizations requires employees who are not only proficient in routine tasks but also capable of adapting to continuous change. This study examines the relationship between High Performance Work Systems (HPWS) and adaptive performance within knowledge-intensive organizational contexts. Using a quantitative research design, data were collected through a cross-sectional survey of employees working in organizations characterized by high reliance on knowledge, expertise, and cognitive skills. The study employed Structural Equation Modeling with a variance-based approach to analyze the relationships between the constructs. The measurement model was assessed to ensure reliability and validity, followed by structural model testing to evaluate the proposed relationship. The results indicate that HPWS has a positive and significant effect on adaptive performance, suggesting that integrated human resource practices contribute to employees’ ability to adjust behavior, learn new skills, and respond effectively to changing work demands. These findings highlight the strategic role of human resource systems in shaping adaptive behavior rather than merely supporting routine performance. The study offers practical implications for organizations seeking to enhance adaptability through coordinated HR practices and contributes to the strategic human resource management literature by extending the understanding of HPWS beyond traditional performance outcomes. Limitations and directions for future research are also discussed.